The effect of Electronic Hand Hygiene Monitoring Towards Hand Hygiene Compliance: A Literature Review - Annisa Rahmi Galleryzki; Hanny Handiyani (International Journal of Nursing and Health Services (IJNHS), 2020)
Hand Hygiene (HH) is the most effective step to reduce the transmission rate of patient care infections. Attempting to increase HH is carried out by using technology and handwashing compliance as an indicator of its success. The study aimed to describe information on technological developments in HH monitoring in hospitals and their effects on the level of compliance of health workers, especially nurses, in conducting HH. This study uses the literature review method, using the Science Direct, Scopus, Ebsco, and PROQUEST databases. The author uses keywords: "electronic hand hygiene monitoring" and "technology of hand hygiene monitoring" in searching the database. The development of technology in HH monitoring has increased in the last decade. The main goal of its development is to reduce the bias that occurs with control by a human. There are three kinds of HH technology, such as wireless tracking technology, auditing video, and chemical fluid sensor. The use of electronic HH monitoring can increase HH compliance, both assessed in terms of quality and quantity. In contrast, until now, there are no tools that can detect HH compliance in all HH WHO's moments. In its development, the successful use of these tools also experienced obstacles